909. Reassessing Pathogens Eligible for the Centers for Disease Control and Prevention's (CDC's) National Healthcare Safety Network (NHSN) "Mucosal Barrier Injury-Laboratory Confirmed Bloodstream Infection" Criteria. (31st December 2020) - Chea, Nora; Magill, Shelley; Benin, Andrea L; Allen-Bridson, Katherine; Dudeck, Margaret; Patel, Prachi; Thomson, Nicola D
Abstract: Background: NHSN Mucosal Barrier Injury-Laboratory Confirmed Bloodstream Infection (MBI-LCBI) includes pathogens likely to cause bloodstream infections (BSI) in some oncology patients. MBI-LCBIs are excluded from central line-associated BSI (CLABSI) reporting to the Centers for Medicare & Medicaid Services. NHSN users have requested other pathogens be added to MBI-LCBI. To make decision, we compared CLABSI pathogen distributions in three NHSN patient location groups. Methods: We analyzed CLABSI data from hospitals conducting surveillance for ≥ 1 month from January 2014–December 2018 in ≥ 1 MBI high-risk location (leukemia, lymphoma, and adult and pediatric hematopoietic stem cell transplant wards). We compared CLABSI pathogen distributions and rates in MBI high-risk locations to medium-risk (solid tumor, adult and pediatric general hematology-oncology wards) and low-risk locations (adult and pediatric medical, surgical, and medical-surgical wards), and used χ2 tests to compare percentages with statistical significance at P ≤ 0.05. Results: Overall, 122 hospitals reported 23, 578 CLABSIs and 12, 961, 921 central line (CL)-days (1.81 CLABSIs per 1, 000 CL-days) (Table). Percentages of CLABSIs due to three MBI-LCBI pathogens ( E. coli, E. faecium, Viridans streptococci) were significantly higher in high- versus low-risk locations, while for other MBI-LCBI pathogens ( K. pneumoniae/oxytoca, E. faecalis, Candida spp., Enterobacter spp.) percentages were significantly lower in high-risk locations (Figure). For pathogens not currently in MBI-LCBI, coagulase-negative staphylococci caused similar percentages of CLABSIs across locations, S. aureus caused a significantly higher percentage of CLABSIs in low-risk locations, while PA caused a significantly higher percentage of CLABSIs in high-risk locations. Table CLABSIs attributed to MBI high-risk, medium-risk, and low-risk locations, NHSN, 2014–2018 Figure Percentages of top 10 pathogen-specific CLABSIs in MBI high-risk, medium-risk, and low-risk locations, NHSN, 2014–2018 Conclusion: Differences in percentages of CLABSIs due to selected pathogens between MBI high-risk and low-risk locations are evident in NHSN data. Lower percentages of Klebsiella and Candida spp. in high-risk locations might be partially due to antimicrobial prophylaxis in oncology patients. Although PA caused a significantly higher percentage of CLABSIs in high-risk locations, the absolute difference was modest. Additional analyses are needed. Disclosures: All Authors : No reported disclosures